Music : an appreciation - Kamien, Roger. 4 0 16; 5 (Boston : McGraw-Hill Higher Education, 2004)
Presents a comprehensive music appreciation course for the high school or college classroom and includes lessons on musical elements, forms, and stylist periods, composers and their lives and styles, as well as representations of their works.
Accompanied by: Multimedia companion version 4.5 : a clear, concise explanation of how to use the tools found on the CD-ROM (12 p. ; 26 cm).
Includes bibliographical references (p. [633]-634), discography (p. [635]-641), and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Music appreciation. -- 20; 20; 2